2017
DOI: 10.5430/ijhe.v6n6p91
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ Attitudes toward Dating Violence: Its Relationship with Sexism and Narcissism

Abstract: In this research, whether the undergraduates' attitude levels towards the dating violence differed in terms of gender, dating relationship status, being exposed to the dating violence and resorting to the dating violence was investigated. The sample of the study was composed of 1171 undergraduates. In the research, "The Attitudes toward Dating Violence Scales, Ambivalent Sexism Scale, Ambivalence toward Men Scale, Narcissistic Personality Inventory, and Personal Information Form" were used as the data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
1
13
1
1
Order By: Relevance
“…Interestingly, in this cultural atmosphere where men showed higher HS, Turkish female students appeared to show higher levels of BS than did male students (this was not statistically significant in the current study but rather reported in previous literature [Erdem & Sahin, ; Ozerdogan et al, ; Tasdemir & Sakalli‐Ugurlu, ]); by contrast, Korean female students showed lower levels of BS than did male students. Under the high levels of HS in men, women's level of BS infers a number of implications.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, in this cultural atmosphere where men showed higher HS, Turkish female students appeared to show higher levels of BS than did male students (this was not statistically significant in the current study but rather reported in previous literature [Erdem & Sahin, ; Ozerdogan et al, ; Tasdemir & Sakalli‐Ugurlu, ]); by contrast, Korean female students showed lower levels of BS than did male students. Under the high levels of HS in men, women's level of BS infers a number of implications.…”
Section: Discussioncontrasting
confidence: 58%
“…Several previous studies conducted in South Korea towards general population have shown similar results – specifically, men had higher ASI scores, including HS scores, than did women (Lee, ; Shim & Endo, ). Moreover, previous studies conducted in Turkey generally found that men's HS scores were higher than were those of women, whereas women's BS scores were higher than were those of men (Erdem & Sahin, ; Ozerdogan et al, ; Tasdemir & Sakalli‐Ugurlu, ).…”
Section: Discussionmentioning
confidence: 93%
“…Renzetti et al (2015) study examined the moderating effects of ambivalent sexism (both hostile and benevolent sexism) on the relationship between alcohol use and intimate partner violence perpetration among a community-based sample of 255 men, and their findings indicate that greater alcohol consumption and higher levels of hostile sexism lead to an increased prevalence of intimate partner violence. Erdem and Sahin's (2017) research identified a significant correlation between participants' attitudes toward dating violence and ambivalent sexism among a sample of 1171 undergraduates. Lila et al (2013) conducted an important study in which they examined the roles of ambivalent sexism and empathy in attitudes toward violence against women among a sample of 404 male police officers.…”
Section: Ambivalent Sexismmentioning
confidence: 98%
“…In addition to the studies on the relationship between the attitudes towards dating violence and subsequent violent behaviors (Flood and Pease, 2009;Foshee, Bauman, Linder, Rice, and Wilcher, 2007;Schumacher and Slep, 2004;Schwartz, Kelley and Kohli, 2012;Slep, Cascardi, Avery-Leaf, and O'Leary, 2001;Stith, Smith, Penn, Ward, and Tritt, 2004), there are also a number of studies suggesting that there is a relationship between aggressive behaviors towards close partners amongst the university students and the beliefs that support violent behavior in the relationship (Archer and Graham-Kevan, 2003;Locke and Richman, 1999;Nabors, Dietz and Jasinki, 2006;Riggs and O'Leary, 1996). According to Erdem and Şahin (2017), on the other hand, individuals' attitudes towards dating violence change in terms of experiencing violence in the relationship. Therefore, the level of acceptance of dating violence in the participants who have experienced violence in their relationships is higher than those who have not experienced violence in their relationships (Erdem and Şahin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Erdem and Şahin (2017), on the other hand, individuals' attitudes towards dating violence change in terms of experiencing violence in the relationship. Therefore, the level of acceptance of dating violence in the participants who have experienced violence in their relationships is higher than those who have not experienced violence in their relationships (Erdem and Şahin, 2017). Previous studies revealed that the participants who had the experience of victims of violence in romantic relationships amongst the young people are more accepting towards dating violence than those who were non-victims of violence (De Puy et.al., 2014;Machado, Caridade, and Martins, 2010).…”
Section: Introductionmentioning
confidence: 99%